The Sunnah between Fundamentalists and Traditionaists: Comparative Analytical Study (Raparin Journal of Humanities (RJH), 2024)
Talking about the Sunnah in the origins of jurisprudence is not a repetition of all that is found in the science of Hadith, but there is a big difference between some of its issues and terms, for example, fundamentalists talk about the authenticity of the Sunnah and the infallibility of the prophets, and the issues of news and construction, but the Traditionaists do not address those issues different definitions between the fundamentalist study of the Sunnah and the study of it in the science of the term Hadith and the differences between them and the consequent differences in the issue of (definition of the Sunnah and the definition of the Companion of the Hadith sent). The origins of jurisprudence were concerned with the search for Sharia evidence, the scholars of Hadith were concerned with the transmission of what was added to the Prophet (peace and blessings of Allaah be upon him), the scholars of jurisprudence concerned with the search for Sharia rulings of imposition, duty, delegate, haram and hatred, and those who are ready to preach and guide have meant everything that the Sharia has ordered or forbidden.